A review on solar greenhouse dryer: Design, thermal modelling, energy, economic and environmental aspects. (15th November 2021) - Srinivasan, G.; Muthukumar, P.
Highlights: A comprehensive review on solar greenhouse dryer is presented. Covers dryer design, mode of operation, product dried and energy aspects. Summaries works reported on solar dryer integrated with PV and thermal storage. Provides a summary on future direction of research on solar greenhouse dryer. Abstract: This article provides an extensive review on design, thermal modelling approaches, and economic, energy and environmental aspects of solar greenhouse dryers developed for drying various agricultural products. Further, the selection and usage of solar photovoltaic panels and thermal energy storage units in the solar greenhouse dryers for achieving continuous and grid-independent drying are discussed in detail. Performances of the various configurations/shapes of the greenhouse dryers in terms of energy requirements are compared. Thermodynamic and thermal modelling studies reported on the performance prediction of solar greenhouse dryers and drying kinetics studies on various agriculture products are summarised. A detailed report on the economic (payback time, cost of the greenhouse dryer, and product drying cost), energy (embodiment energy, specific energy consumption) and environmental (CO2 emission, CO2 mitigation, and carbon credit) aspects of the solar greenhouse dryer based on the dryer type, mode of operation and product dried are presented.